Test of Some Aspects of Modelling the Sorption of Hydrophobic Compounds in Soils - Bogusław Buszewski; Radosław Zbytniewski (Adsorption Science & Technology)
A study was carried out on the sorption of the herbicide linuron in podzolic soil (one of the typical soils of Poland), the sorption isotherms being obtained using batch equilibrium studies. Modelling sorption phenomena involving the interactions of chemicals and particularly herbicides is very difficult because of the strong heterogeneity of the soil matrix. The present work presents the results of applying the most common models, i.e. Freundlich and Linear, as well as the newer concept of the Dual Reactive Domain model. The data obtained were validated using various statistical and chemometric methods. The results suggest that applying the non-linear least-squares method to obtain isotherm parameters gave a much better description of the sorption phenomena than often obtained using linear transformations of the adsorption equations. The study also showed that appropriate weighting schemes should be included in any model calculations. To test the goodness-of-fit of the model to the experimental data both the correlation coefficient and the Residual Root Mean Square Error were obtained. The models were also compared using the Extra Sum of Squares Principle statistical test.